2017
DOI: 10.3389/fnins.2017.00653
|View full text |Cite
|
Sign up to set email alerts
|

The Alteration of Irisin—Brain-Derived Neurotrophic Factor Axis Parallels Severity of Distress Disorder in Bronchial Asthma Patients

Abstract: Distress disorder (a collective term for generalized anxiety disorder and major depressive disorder) is a well-known co-morbidity of bronchial asthma. The irisin—brain-derived neurotrophic factor (BDNF) axis is a pathway that influences several neurobehavioral mechanisms involved in the pathogenesis of distress disorder. Thus, the aim of the present study was to quantify the serum irisin and BDNF concentrations in order to investigate the possible link between the irisin/BDNF axis and distress disorder in an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 81 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…Moreover, the exclusion criteria of this study were quite restrictive and future studies should be conducted on much larger samples of asthma patients, taking into account the effects of comorbidities and medications, to reflect the real-world data. As the role of depression in asthma is an ongoing area of research [ 84 , 85 , 86 ], it would be important to also incorporate these patients in future studies. On the other hand, the present study included an adequate number of participants in order to have statistical power and to observe statistically significant associations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the exclusion criteria of this study were quite restrictive and future studies should be conducted on much larger samples of asthma patients, taking into account the effects of comorbidities and medications, to reflect the real-world data. As the role of depression in asthma is an ongoing area of research [ 84 , 85 , 86 ], it would be important to also incorporate these patients in future studies. On the other hand, the present study included an adequate number of participants in order to have statistical power and to observe statistically significant associations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies including healthy individuals and other patient populations reported serum BDNF levels spanning over four orders of magnitude, ranging from 0.005 ng/ml to 280 ng/ml, [7174] using different ELISA kits. Our group has formerly reported serum BDNF levels of 345.6 ng/mL (IQR 294.20–387.90 ng/mL) and 314.46 ± 118.68 ng/mL in cohorts of chronic obstructive pulmonary disease patients [75] and bronchial asthma [76], respectively. To the best of our knowledge there are no reports concerning the serum level of irisin in OSHAS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is an antidepressant (Blumenthal et al, 1999; Cunha et al, 2013), and irisin has been linked to the antidepressant effects of exercise. Reduced irisin levels are associated with mood impairment and reduced BDNF levels in humans (Papp et al, 2017; Szilasi et al, 2017), and increased circulating concentrations of irisin have been shown to have antidepressant effects in mice (Siteneski et al, 2018). A possible mechanism for the antidepressant effect is the activation of the PGC-1α/BDNF pathway by irisin after exercise (Wrann et al, 2013).…”
Section: The Exercise-induced Release Of Irisin and Its Neuroprotectimentioning
confidence: 99%